Facial emotion processing in major depression: a systematic review of neuroimaging findings - Stuhrmann, Anja (BioMed Central, 2011)
BACKGROUND: Cognitive models of depression suggest that major depression is characterized by biased facial emotion processing, making facial stimuli particularly valuable for neuroimaging research on the neurobiological correlates of depression. The present review provides an overview of functional neuroimaging studies on abnormal facial emotion processing in major depression. Our main objective was to describe neurobiological differences between depressed patients with major depressive disorder (MDD) and healthy controls (HCs) regarding brain responsiveness to facial expressions and, furthermore, to delineate altered neural activation patterns associated with mood-congruent processing bias and to integrate these data with recent functional connectivity results. We further discuss methodological aspects potentially explaining the heterogeneity of results. METHODS: A Medline search was performed up to August 2011 in order to identify studies on emotional face processing in acutely depressed patients compared with HCs. A total of 25 studies using functional magnetic resonance imaging were reviewed. RESULTS: The analysis of neural activation data showed abnormalities in MDD patients in a common face processing network, pointing to mood-congruent processing bias (hyperactivation to negative and hypoactivation to positive stimuli) particularly in the amygdala, insula, parahippocampal gyrus, fusiform face area, and putamen. Furthermore, abnormal activation patterns were repeatedly found in parts of the cingulate gyrus and the orbitofrontal cortex, which are extended by investigations implementing functional connectivity analysis. However, despite several converging findings, some inconsistencies are observed, particularly in prefrontal areas, probably caused by heterogeneities in paradigms and patient samples. CONCLUSIONS: Further studies in remitted patients and high-risk samples are required to discern whether the described abnormalities represent state or trait characteristics of depression.